Public support for Latin American integration: an econometric model for the assessment of individual and contextual factors - Jara Ibarra, Camila (Estudios Internacionales, 2014)
The purpose of this article is assessing factors that affect Latin American people’s opinions on regional integration. By means of hierarchical logistic regressions, variables at both individual and national level were considered and fixed and random effects were taken into account. All variables included at the individual level, both socio-demographic and ideological, were found to be significant factors as well as some cross-level interactions. Likewise, there is a significant country effect on the probability of Latin American people supporting integration.